The quality of local democracy: an institutional analysis - Sousa, Luis de (2022)
Much of the literature on quality of democracy is case study-oriented and focused on nation states. Theoretical work and, in particular, comparative empirical research on the quality of local democracy are less advanced. This paper contributes to our understanding of how democracy works from below. It develops a conceptual framing and employs a multidimensional index of the quality of democracy across all 278 municipalities in mainland Portugal by focusing on procedural dimensions of democratic performance at three levels of legitimacy: input, throughput, and output. Regression analysis is then used as a preliminary test of the usefulness of these measures of quality of local democracy and to uncover associations between them and a range of political and socioeconomic factors. The results suggest that municipalities led by independent mayors, with larger populations and higher levels of multiculturalism are likelier to be associated with ‘better’ local democracy.